Exploring graduate employability through self-determination and constructivist perspectives: A tracer study of postgraduate alumni - Rachelle Wapaño, Mary (Journal of Interdisciplinary Studies in Education, 2026)
This research investigates graduate employability and competency relevance through the application of Self-Determination Theory (SDT) and Constructivist Learning Theory as theoretical frameworks. Survey instruments were designed and analyzed based on SDT autonomy, competence, and relatedness dimensions, while constructivist principles helped explain how academic learning translates into professional practice. The research employed a tracer study method to gather data from 147 master’s and doctoral alumni of a private higher education institution. The findings indicate that 91% of respondents maintain full-time employment, and 62.6% confirm that their current work matches their graduate education. Alumni participants reported significant career progression and extensive use of transferable abilities. The research provides implications for curriculum review, quality assurance, and theoretical integration in graduate outcome assessments.